IMPLEMENTING CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH TO IMPROVE STUDENTS’ UNDERSTANDING OF MATHEMATIC CONCEPTS - Minarni Minarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the large number of students who found it difficult to understand the concept of mathematics because mathematics was generally an abstract subject. For this reason, the teacher must strive for learning to be concrete by applying learning that could relate the concept to the students’ real life. One of the efforts was implementing contextual teaching and learning approach to present learning that linked abstract concepts to the students' daily life. The type of this research was classroom action research conducted in class IV/A SDN 003 Sungai Salak. The number of research subjects was 24 students. The instrument used in this research was a multiple choice test. The results showed that students' understanding of mathematical concepts in the first cycle was 68.61 in which 17 students reached the KKM (70.83%). In cycle II, the students' understanding of mathematical concepts increased to 71.11 with the classical completeness of 83.33% in which as many as 20 students achieved the specified completeness (KKM). In conclusion, the implementation of contextual teaching and learning approach improved the students’ understanding of the mathematical concepts at grade IV / A of SDN 003 Sungai Salak on the subject of circumference and area of simple flat shapes.